Comparison of Public, Non-Profit and Private Hospitals - Bärbel Held (Institute of Economic Research (IER), 2014)
The health care system in Germany is undergoing a phase of transformation. The resulting challenges and fields of action for the hospitals were described as one outcome of a scenario analysis conducted by the author. These include, for example, setting up new organisation structures, professionalising management competence or also developing a comprehensive quality management system. In the following analysis, the hospitals are to be described and compared to one another in terms of their initial conditions regarding these fields of action. The question at the focus is which different prerequisites and options the clinics have subject to their organisational structure.
Keywords: I11; I12; I13; P36; 330; analysis; comparison; health care; hospitals; soft budget constraint syndrome (SBC)